2014
DOI: 10.1111/j.1600-0587.2013.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Scale dependency in the functional form of the distance decay relationship

Abstract: We examine a novel mathematical approach which posits that the decay of similarity in community composition with increasing distance (aka distance decay) can be modeled as the sum of individual species joint-probability vs distance relationships. Our model, supported by analyses of these curves from three datasets (North American breeding birds, North American taiga plants, and tropical forest trees), suggest that when sampling grain is large enough to avoid absences due to stochastic sampling effects, and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 55 publications
1
90
0
Order By: Relevance
“…The fact that species replacement, rather than change in species richness, was the main driver of compositional change across the scale gradient offers important insights for the underlying processes driving β‐diversity at different spatial scales. It also has implications for both our understanding of spatiotemporal dynamics of biodiversity change and conservation (Baselga , Dornelas et al , Magurran et al , McGill et al , Socolar et al 2016), highlighting that substantial changes in community composition might be occurring, despite species richness remaining seemingly stable. A recent meta‐analysis by Soininen et al (2017) also found turnover to be the dominant component of β‐diversity across different latitudes, spatial extents and taxa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that species replacement, rather than change in species richness, was the main driver of compositional change across the scale gradient offers important insights for the underlying processes driving β‐diversity at different spatial scales. It also has implications for both our understanding of spatiotemporal dynamics of biodiversity change and conservation (Baselga , Dornelas et al , Magurran et al , McGill et al , Socolar et al 2016), highlighting that substantial changes in community composition might be occurring, despite species richness remaining seemingly stable. A recent meta‐analysis by Soininen et al (2017) also found turnover to be the dominant component of β‐diversity across different latitudes, spatial extents and taxa.…”
Section: Discussionmentioning
confidence: 99%
“…not spatially explicit), while the second approach typically regresses pairwise site comparisons vs geographic distance (distance–decay relationship (DDR); Nekola and White 1999, Morlon et al ). DDR are often well fitted by exponential or power law curves, and β‐diversity is then summarized as the rate of change from this curve (Nekola and McGill ). Additionally, β‐diversity may reflect two underlying phenomena – turnover and nestedness.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these presence/ absence tables was used to compute the similarity between pairs of territories using the Simpson's similarity index (1 − β sim  a/[a + min(b,c)]) in R package 'betapart' (Baselga and Orme 2012), where a is the number of species present in both territories, and b and c the number of species unique to one or another, respectively. Theory suggests that the negative exponential model should better describe distance decay patterns at large spatial scales (Nekola and McGill 2014), as the one we are studying. Then, for each taxon and region (i.e.…”
Section: Statistical Analysesmentioning
confidence: 94%
“…Here we compare species turnover and accumulation patterns in comparable temperate (Slovakia and the Czech Republic) and tropical (Malaysian Borneo) land snail datasets. Such directional change in the regional species pool is supported by extensive fossil evidence (Ložek 1964) and is further documented by the exponential form of the temporal DD relationship (Nekola and McGill 2014). Highly significant temporal distance decay (DD) in species composition was noted ( Fig.…”
mentioning
confidence: 53%
“…Such directional change in the regional species pool is supported by extensive fossil evidence (Ložek 1964) and is further documented by the exponential form of the temporal DD relationship (Nekola and McGill 2014). Observed turnover in the temperate system was expected given regional biome change from the cold and dry LGM to wet and warm modern.…”
mentioning
confidence: 78%